2016
DOI: 10.1007/s10973-016-5371-4
|View full text |Cite
|
Sign up to set email alerts
|

DSC measurements of blood plasma on patients with chronic pancreatitis and operable and inoperable pancreatic adenocarcinoma

Abstract: Currently, the most examinations and markers are of limited diagnostic and prognostic value in chronic inflammation of the pancreas and its malignant tumorous disease. The purpose of this pilot study was to measure thermal changes of blood plasma by differential scanning calorimetry (DSC) method on patients with chronic pancreatitis, and with operable or inoperable pancreatic adenocarcinoma. The study involved chronic pancreatitis patients (n = 5), in whom had to perform surgery due to any complications. In ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…With this, deconvolution processes could be shown that mostly the thermodynamics of main plasma proteins are changed. Similarly, our previous investigations showed permanent appearance of plasma thermal changes also [9][10][11][12]. In fact, these observations are true for not only individual disease groups, but also in known malignant symptoms and in its different severity stages.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…With this, deconvolution processes could be shown that mostly the thermodynamics of main plasma proteins are changed. Similarly, our previous investigations showed permanent appearance of plasma thermal changes also [9][10][11][12]. In fact, these observations are true for not only individual disease groups, but also in known malignant symptoms and in its different severity stages.…”
Section: Discussionsupporting
confidence: 79%
“…It seems for us that in the last 60-70 years, research of blood tests has not brought the breakthrough in diagnosing and monitoring of tumors. In the last 10 years, many our research and previous studies from others have highlighted the potential applicability of the DSC technique in the diagnosis of certain tumors [7][8][9][10][11]. After positive results of the first experiments to elucidate the clinical utility of DSC, it is important to establish the sensitivity and specificity of the method.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal profiles of heat capacity changes for aqueous solutions of human blood serum from athletes have been described and discussed in details earlier [37]. Comparing DSC curves of athletes serum diluted with distilled water (pH 6.5-7.0) with curves reported for serum/plasma of healthy persons where the final pH of solutions was in the range 7.2-7.5 [25][26][27][29][30][31][32][33][34][35][36], distinct differences are visible. The main origin of these differences is probably the thermal denaturation profile of fatty acid-free fraction of albumin.…”
Section: Resultsmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) has recently been found useful in the support of various medical diagnoses [25][26][27][28][29][30][31][32][33][34][35][36] by analysis of plasma or serum heat capacity changes in the temperature range of protein components thermal denaturation. DSC profiles of biofluids are able to reflect their modified composition, changes in thermal stability of major proteome components resulting from covalent modifications or binding interactions involving disease biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The modern DSC was shown recently as valuable, harmless tool for disease diagnosis. This method enables to distinguish any slight differences between thermodynamic parameters of cancer and non-cancer diseases and norm [23][24][25][26][27][28][29][30][31]. Our earlier DSC studies [32,33] of athlete's serum indicate that this technique may be also applied in sports medicine to support sports training.…”
Section: Introductionmentioning
confidence: 99%